Stem resources repository helps improve teaching across Europe.
European students are less and less interested in science, technology, engineering and mathematics (STEM). In fact, the EU is already running short of STEM professionals. To help Member States solve this problem, the EU-funded SCIENTIX 2 project provides strategies for the wide uptake and dissemination of 'Inquiry-based science and maths education' (IBSME), along with other methdologies known to improve the quality of science education.